(untitled) (Studia Archaeologica, 2026)
This paper presents the results of a 2025 reconnaissance and high-precision survey of earthen-walled sites located in the Kherlen and Onon river basins. The study aimed to determine the overall morphology and internal spatial organization of these sites with a high degree of accuracy through the integrated application of GNSS static measurements, drone-based photogrammetry (orthophoto), Digital Elevation Models (DEM), and GIS analysis. Metric analysis of sites including Tsenkheriin Gol fortress, the Western and Eastern fortresses, Ovootiin Baruun Khavtsal, and Kherlen Bars II demonstrates the use of standardized planning principles when their dimensions are converted into the ancient Chinese unit chi (尺). The results suggest that fortifications associated with the Xiongnu period were likely constructed using the Han dynasty standard (1 chi = 0.233 m), whereas Khitan-period urban sites appear to have employed the Tang dynasty standard (1 chi = 0.296 m). In certain cases (e.g., Kheree Gököl), the possible use of measurement units corresponding to the Mongol Empire period is proposed. The layout of the Eastern Fortress—particularly its gate outworks and street system—corresponds closely to known characteristics of Khitan urban planning and may be associated with administrative centers mentioned in historical sources. Ovootiin Baruun Khavtsal, with its centrally organized architectural complex, shows structural similarities to elite Xiongnu compounds. Although no Xiongnu earthen fortifications were confirmed in the Onon basin during this survey, the area remains a significant target for future investigation. The combined use of drone survey and GNSS control points reduced measurement error to within 3%, demonstrating the effectiveness of this methodology for establishing chronological frameworks and reconstructing planning principles of earthen-walled settlements. Хэрлэн голын сав дагууд орших шороон хэрэмт дурсгалд хийсэн хэмжилт судалгаа Хураангуй. Энэхүү өгүүлэлд Хэрлэн голын сав дагууд орших шороон хэрэмт дурсгалуудад хийсэн хайгуул, нарийвчилсан хэмжилт судалгааны үр дүнг хэлэлцүүлж байна. Судалгаанд GNSS хэмжилт, дрон зураглал (orthophoto), дижитал өндөршлийн загвар (DEM), GIS боловсруулалтыг хослуулан ашиглаж, дурсгалын хэлбэр хэмжээ, дотоод зохион байгуулалтыг өндөр нарийвчлалтай тогтоохыг зорьсон юм. Судалгаанд Цэнхэрийн голын хэрэм, Баруун болон Зүүн хэрэм, Овоотын баруун хавцал, Баруун дөрөөгийн хэрэм зэрэг дурсгалд эртний “尺 (чи)” нэгжид хөрвүүлэн тооцсон төлөвлөлтийн зарчим хэрэглэснийг тодруулав. Үр дүнгээс харахад Хүннүгийн үед хамаарах дурсгал нь Зүүн Азид өргөн ашиглагдаж байсан Хань улсын хэмжих нэгж болох 1 чи=0.233 м, харин Хятаны үеийн хотуудад Тан улсын үед ашиглаж байсан 1 чи=0.296 м хэмжээс, Хэрээ гөхөл дурсгалд Монголын эзэнт гүрний үеийн чи-ийг ашигласан байх магадлал өндөр гэсэн таамаг дэвшүүлэв. Судалгаанд дрон ба GNSS-ийг хослуулах арга хэрэглэснээр хэмжилтийн алдааг 3%-иас дотогш барих боломжтойг баталж, шороон хэрэмт хотуудын он цаг, төлөвлөлтийн зарчмыг тодорхойлоход зохимжтой арга зүй болохыг харууллаа. Түлхүүр үг: Хүннү, Хятан, шороон хэрэмт дурсгал, GNSS, Orthophoto, Dem, “Чи 尺”